Facilitators and barriers to behavior change in overweight and obesity management using the COM-B model - Timkova, Vladimira; Minarikova, Daniela; Fabryova, Lubomira; Buckova, Jana; Minarik, Peter; Katreniakova, Zuzana; Nagyova, Iveta (Frontiers in Psychology, 2024)
Increasing overweight and obesity rates represent one of the global public health challenges. COM-B is a theoretical model used to identify areas to target to achieve behaviour change. It identifies three factors that are needed for any behaviour to occur: capability, opportunity, and motivation. We aimed to assess the potential facilitators and barriers to behaviour change in weight management using the COM-B. The study included 139 people with overweight and obesity (mean age 48.81±14.49 years; 64.5% female; body mass index 32.64±6.51 kg/m2; waist-to-height ratio 0.62±0.10) from primary care settings. All participants completed the Brief Measure of Behavior Change (COM‐B), the General Self-Efficacy Scale (GSE), the Rosenberg Self-esteem Scale (RSE), and the Overall Evaluation of Health (OEH). Multiple linear regression was performed to analyse the data. The associations between sociodemographic and clinical variables and COM-B domains attenuated or were no longer significant when psychological resources were added to the regression models. Self-efficacy was identified as a stronger facilitator of health behaviour change (p<.001) when compared to self-esteem (p<.05). No associations between automatic motivation and psychological resources were identified, however. Automatic motivation was found to be associated with higher age, being in a relationship, and better health. Behavioural interventions for weight management should specifically target different components of COM-B. Self-efficacy and self-esteem may play a significant role in individual capabilities, opportunities, and reflective motivation and should be included in tailored public health interventions. Health programs targeting younger and single people, and people with chronic conditions may help to promote sustainable behaviour change.